Public sector efficiency : evidence for Latin America - Afonso, António (2022)
We compute Public Sector Performance (PSP) and Public Sector Efficiency (PSE) indicators and Data Envelopment Analysis (DEA) efficiency scores for a sample of twenty-three Latin American and Caribbean Countries (LAC) to measure efficiency of public spending for the period 2001-2010. Our results show that the PSE is inversely correlated with the size of the government, while the efficiency frontier is essentially defined by Chile, Guatemala, and Peru. Moreover, on average, output quantities could theoretically be proportionally increased by 19 percent with the same level of inputs. In addition, the performed Tobit analysis suggests that more transparency and regulatory quality improve the efficiency scores, while more transparency and control of corruption increase output-oriented efficiency.